Effect of livestock and seasonal variation on floristic composition and plant biomass in wetlands of the central western coast of the Gulf of Mexico - Rodríguez-Medina, Karla; Moreno-Casasola, Patricia; Yañez-Arenas, Carlos (Instituto de Ecología, A.C., 2017)
Background and Aims: Wetlands are highly productive ecosystems, which provide many environmental services. However, they are one of the most threatened due to human activities such as agriculture and livestock. Mexico has lost 62% of its wetlands and specifically those of the central coast of the Gulf of Mexico are being affected due to livestock pressure. There are very few studies about the subject, so in this paper we analyze the effect of livestock and seasonality on floristic composition, above ground biomass (AB) and below ground biomass (BB) of the Alvarado lagoon, Veracruz, Mexico.Methods: We selected two working locations, and in each locality chose two sampling sites. In each site, we placed eight 1 m² plots of four different locations (half were fenced to keep out livestock). For an entire year we obtained species richness and diversity, and data on vegetation cover, as well as AB and BB. With the data obtained, we calculated the Relative Importance Value (RIV) by species and the relative replacement rate of species.Key results: Total richness resulted in 29 species. A disturbance gradient was observed, with the best conserved sites in Río Blanco. In most sites, species richness was significantly higher in rainfall and species with high RIV were typical wetland species, although there were dominant grasses in both climatic seasons. BB was significantly higher in one location of Rio Blanco, and AB in one location of Rio Blanco and in one from Rio Limon. During the rainy season, AB was higher in half of the sites.Conclusions: We conclude that freshwater wetlands can retain their ecological functions in the presence of livestock as long as the impact is low. Even if there is cattle grazing with a controlled management, it can promote diversity of native wetland species and limit the growth of invasive grasses.